Pengaruh Perlakuan Alkali terhadap Kekuatan Tarik Komposit Epoxy Berpenguat Serat Bagasse - Enggar Dyah Nailufah Haryanti; Budianto Budianto; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Sugarcane is a plant that is used as the main ingredient for making sugar. On the other hand, the utilization of bagasse is not optimal, where on average, bagasse is only used as fuel for the production process and for power generation. Bagasse fiber can be processed for the manufacture of composites. The benefits of bagasse fiber as a composite are quite good mechanical properties, noncorrosive, easy to obtain and environmentally friendly. In addition, when compared to synthetic fibers, composites with natural fibers are lighter. Synthetic fiber also has some drawbacks, namely it can cause skin irritation and injure the lungs during the production process. This time, a research was conducted on the effect of alkaline treatment on bagasse fiber. The variation of NaOH concentration is 0% and 3% for 1 hour. The composite was made using 5 mm short fibers arranged randomly and Chopp Matt fibers with a composition of 35%:65%. The composite with the highest tensile strength was obtained at the delignification process variation of 3% NaOH concentration with a tensile strength of 38.25±5.79 MPa. Then the lowest tensile strength occurred at 0% NaOH concentration variation with a tensile strength of 18.74±3.02 MPa.